Pengaruh Strategi Generik terhadap Kinerja Perusahaan (Studi pada Bank Umum) - Rustamblin, Daly; Thoyib, Armanu; Zain, Djumilah (Universitas Brawijaya, Indonesia, 2013)
The purpose of this study is to examine the relationship between competitive strategy andorganisational performance and to determine the applicability of Porter's generic strategies in explainingits different effects to the organisational performance. There are three independent variables analyzed inthis study: differentiation strategy, cost leadership and integrated strategy, while the dependent variable isthe performance of the organization which is a subjective measure of objective's fulfillment and relativecompetitive performance. The data has been collected then analyzed using linear multiple regressionanalysis. The results of this study indicates that the application of a generic strategy has an importantinfluence on the bank's performance, while the selection of differentiation strategy has a better impact onthe bank's performance in comparison with the cost leadership and integrated strategies.